R.I.P.D. 2 : rise of the damned [videorecording (DVD)] - Leyden, Paul A., 1972-; Klein, Andrew; Donovan, Jeffrey; Mitchell, Penelope; Choi, Jake; Brake, Richard, 1964-; Lenkov, Peter M. (Universal Studios, 2022)
The Wild West has gone to Hell, literally, and the world's best hope of being saved lies in the gun-slinging hands of Sheriff Roy Pulsipher as he becomes the newest officer for the Rest In Peace Department (R.I.P.D.) enforcing the afterlife's laws. If the Old West was wild while he was alive, wait until Roy sees how weird it gets once he dies. Roy thought joining the R.I.P.D. would give him a chance to revisit his daughter and solve the mystery of his murder. Instead, he has his holsters full of havoc and hellfire when he's given a mission to stop a dangerous demon from opening a portal to the underworld. The fate of the living and the dead now depends on Roy and his partner Jeanne, a mysterious swordswoman, as cowboys clash with creatures and undead insanity unleashes apocalyptic chaos.